COVID-19: ASSESSING THE PERFORMANCE OF THE PROPERTY AND REAL ESTATE COMPANIES - Munawaroh, Siti; Nurhidayati, Safitri (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This research is a quantitative research type with the aim of testing the impact of Covid-19 on the financial performance of Property and Real Estate companies listed on the IDX. The research sample was selected using purposive sampling method with a population of 62 companies. Data collection is done by using the Documentation technique. In this study the data source used is secondary data. The analytical methods used in this study include: By using the Normality Test, Paired Test, Paired Sample Correlations Test and Paired Sample Test. The results of the study show data using statistical calculations through the Statistical Package For The Social Science (SPSS) application regarding the impact of Covid-19 on the financial performance of property and real estate companies listed on the IDX using Liquidity Ratio (CR), Solvency (DER), Profitability (ROA), and Activity Ratio (TATO) to measure the comparison of financial performance before and after the announcement of the COVID-19 pandemic in Indonesia. The results of the study show that: Covid-19 has an impact on the company’s financial performance as measured by Total Asset Turnover.